(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Stature is one of the used parameters for identification in forensic anthropology. This study aimed to develop a formula to estimate the stature of children using anthropometric measurements. Ten anthropometric measurements were measured for 350 students randomly selected from two primary schools. The arm span exceeds height at old ages and the majority of measurements were higher in girls. A strong correlation was found for stature and majority of measurements.